PEMANFAATAN BAHAN ALAMI DALAM PELATIHAN PEMBUATAN TOTEBAG ECOPRINT PADA IBU-IBU PKK BANJAR TEGAL ASAH DESA SANUR KAJA - I Komang Widnyana; Ananta Maura Isnaini; T. Asima Sulys Simanjuntak; I Komang Sukendra (LP3M Universitas PGRI Mahadewa Indonesia, 2025)
Banjar Tegal Asah is located in Sanur Kaja Village, possesses abundant local potential, particularly in the form of uniquely patterned leaves that have yet to be optimally utilized by the community, especially by the women’s PKK group. Limited access to skill-based training and low awareness regarding the use of biological resources as creative products remain major obstacles to developing an environmentally based creative production. In response to this issue, students from Pendidikan Profesi Guru (PPG) program, as part of their Projek Kepemimpinan course, implemented an ecoprint tote bag training program using natural materials available in the surrounding environment. This community service initiative aimed to provide a solution through ecoprint training, a natural dyeing technique that transfers the shape and pigment of plants onto fabric. The method used was a participatory approach based on experiential learning, carried out in five main stages, including socialization, skills training, technology application, mentoring, and evaluation. The training results showed a significant increase in participants’ skills and understanding. Most participants were able to independently apply the ecoprint technique and demonstrated improved comprehension of ecoprint principles and environmental conservation. This program not only produced artistic ecoprint tote bags but also fostered self-confidence, entrepreneurial spirit, and ecological awareness among the participants.